2022
DOI: 10.1080/21645515.2021.2021711
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance on the adverse events following immunization with the pentavalent vaccine in Zhejiang, China

Abstract: Objectives The aim of this study is to describe the reporting rate of adverse events following immunization (AEFI) with pentavalent vaccine: diphtheria-pertussis-tetanus-poliomyelitis-Haemophilus influenzae type b (DPT-IPV/Hib), and to determine whether the reporting rate of AEFI following DPT-IPV/Hib was higher than the average level of the other vaccines. Methods Review and describe the AEFI reported to national adverse event following immunization surveillance system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…We observed no significant difference in reported AEFI incidence between boys and girls, which is generally consistent with previous reports ( 23 , 24 ). We found that the reported incidence of AEFI in 2020 was highest from 2019 to 2022.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed no significant difference in reported AEFI incidence between boys and girls, which is generally consistent with previous reports ( 23 , 24 ). We found that the reported incidence of AEFI in 2020 was highest from 2019 to 2022.…”
Section: Discussionsupporting
confidence: 93%
“…Their argument is the recipients and their guardians pay more attention to the reaction after the first dose of vaccine ( 25 , 26 ). However, there are some studies that support our conclusions ( 24 , 27 ). The view they take is the subsequent dose was more likely to cause allergic reactions due to the body sensitization by the early dose.…”
Section: Discussionsupporting
confidence: 68%
“…A 5-year persistence study of EV71 vaccination showed that the GMTs of EV71 neutralizing antibody of the vaccine group was significantly higher than the placebo-controlled group (369.57 vs. 55.58, p < 0.01), and EV71 antibodies still maintained good immune persistence 5 years after two doses of immunization [12]. A large-scale safety monitoring study in Zhejiang Province found that the reported rate of AEFI was 267.90 per 100,000 persons, and there were no serious AEFI cases, and most common reactions were fever, redness, and induration, indicating that EV71 vaccine was safe [13]. A real-world effectiveness study showed that the average morbidity rate of EV71-related HFMD in Chengdu (Sichuan Province) in 2017-2018 was 60% lower than that in 2011-2017 when the EV71 vaccine was not available, and the number of severe HFMD cases was 52% lower, demonstrating that EV71-related HFMD significantly decreased after vaccination [14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the public or the caregivers could notify any of the above authorized reporters to report an AEFI. AEFI reports were gathered by local, county-level CDCs, which were responsible for completing AEFI case reporting cards and submitting data to the national AEFI surveillance system ( 25 ). A single AEFI report might be assigned more than one term and be referred to more than one suspected vaccine.…”
Section: Methodsmentioning
confidence: 99%